PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI TEKS PROPOSAL DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS XI MIPA 4 SMA NEGERI 7 DENPASAR (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine the ability and response of students in the application of discovery learning models to improve learning outcomes in writing proposal texts. This type of research is classroom action research which was conducted from January to February 2020. The research subjects were students of class XI MIPA 4 SMA Negeri 7 Denpasar for the 2019/2020 school year. The object of this research is to write a proposal text, with discovery learning learning model in improving Indonesian learning outcomes. The research carried out four main activities: planning, acting, observing, and reflecting. The results of the research on the initial reflection action were 63.69 with a low predicate, and increased in the first cycle to 71.67 with a sufficient predicate and increased again in the second cycle to 79.17 with a good predicate with a classical number of 34 or 94.44%. The results of student observations in the first cycle had an average value of 69.44 with a sufficient predicate and increased in the second cycle an average value of 80.56 with a high predicate with a classical number of 34 students or 94.44%. The application of the discovery learning learning model can improve the ability to write proposal texts and the responses of class XI MIPA 4 SMA Negeri 7 Denpasar in the 2019/2020 academic year